2016
DOI: 10.1002/ardp.201600145
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Cyclooxygenase Inhibition, Anti‐Inflammatory Evaluation, and Ulcerogenic Liability of New 1,3,5‐Triarylpyrazoline Derivatives Possessing a Methanesulfonyl Pharmacophore

Abstract: A new series of 1,3,5-triarylpyrazolines 13a-l was synthesized and all prepared compounds were evaluated for their in vitro COX-1/COX-2 inhibitory activity and in vivo anti-inflammatory activity. All test compounds were more selective for the COX-2 isozyme and showed good in vivo anti-inflammatory activity. Compound 13h was the most COX-2 selective compound (COX-2 selectivity index (SI) = 10.23) and the most potent anti-inflammatory derivative (ED = 60.1 µmol/kg) in comparison with celecoxib (COX-2 SI = 9.29 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The pharmacological activity of NSAIDs is related to the suppression of prostaglandin (PG) biosynthesis from arachidonic acid by inhibiting the cyclooxygenase (COX) enzymes. Prostaglandins that cause fever, pain, and inflammation are formed by cyclooxygenase‐2 (COX‐2) isoenzyme whereas others regulate beneficial gastrointestinal cytoprotection due to cyclooxygenase‐1 (COX‐1) mechanism . A prominent side effect on chronic use of NSAIDs is generally attributed to two main factors: decreased tissue prostaglandin production and local irritation by the direct contact of carboxylic acid (COOH) moiety of NSAIDs with GI mucosal cells .…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological activity of NSAIDs is related to the suppression of prostaglandin (PG) biosynthesis from arachidonic acid by inhibiting the cyclooxygenase (COX) enzymes. Prostaglandins that cause fever, pain, and inflammation are formed by cyclooxygenase‐2 (COX‐2) isoenzyme whereas others regulate beneficial gastrointestinal cytoprotection due to cyclooxygenase‐1 (COX‐1) mechanism . A prominent side effect on chronic use of NSAIDs is generally attributed to two main factors: decreased tissue prostaglandin production and local irritation by the direct contact of carboxylic acid (COOH) moiety of NSAIDs with GI mucosal cells .…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones have been receiving increasing attention due to their wide range of biological activities along with the COX inhibitory activity. [ 16–19 ] A literature survey revealed that they show their anti‐inflammatory activity through suppression of NO, COX‐2, TNF‐α, IL‐1β, inducible nitric oxide synthase (iNOS), and other essential cytokines. [ 20–23 ] Zarghi et al [ 24–26 ] reported a novel class of compounds possessing an acyclic 1,3‐diarylprop‐2‐en‐1‐one structural template as COX inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Among the family of biologically active heterocycles, special interest has been given to pyrazole‐containing compounds as potential anti‐inflammatory, antinociceptive, and antipyretic agents especially after the discovery of antipyrine at 1884 as the first anti‐inflammatory pyrazole analog. As a consequence, a tremendous number of pyrazoles has been prepared, biologically investigated, and some of them have been introduced clinically.…”
Section: Introductionmentioning
confidence: 99%